Colonic transit in children and adolescents with chronic constipation - Rafael L.M.L. Carmo; Raquel P.M. Oliveira; Antonio E.A. Ribeiro; Mariana C.L. Lima; Bárbara J. Amorim; Antonio Fernando Ribeiro; Celso D. Ramos; Joaquim M. Bustorff-Silva; Elizete A. Lomazi (Elsevier, 2015)
OBJECTIVE: The aim of this study was to assess clinical features and colonic transit patterns in Brazilian children with refractory constipation.METHODS: From 2010 to 2013, 79 constipated patients received follow-up care in a tertiary hospital. Of these patients, 28 (aged 8-14 years) were refractory to conventional therapy and underwent a simplified visual method of nuclear colonic transit study, by ingestion of a liquid meal containing 9.25 MBq/kg of 99mTc-phytate. Abdominal static images were taken immediately and at two, six, 24, 30, and 48 h after ingestion for qualitative analysis of the radio marker progression through the colon.RESULTS: Two patterns of colonic transit were found: slow colonic transit (SCT,n = 14), when images at 48 h showed a larger part of the tracer remained in proximal and transverse colon, and distal retention (DR, n = 14), when after 30 h, the radio isotope passed the transverse colon and was retained in the rectosigmoid up to 48 h. The SCT and DR group included, respectively, nine and ten males; median ages in the nuclear study of 11 and 10 years, p = 0.207; median duration of constipation of seven and six years, p = 0.599. Constipation appearing during first year age (p = 0.04) and report of soft stools (p = 0.02) were more common in SCT patients. Palpable abdominal fecal impaction was found only in DR group. Appendicostomy for antegrade continence enema was successful in 4/12 (30%) of SCT patients (median follow-up: 2.4 years).CONCLUSION: Nuclear transit study distinguished two colonic dysmotility patterns and was useful for guiding refractory patients to specific therapies.